Relações exteriores da Guiné-Bissau: um estudo das relações bilaterais Guiné-Bissau/Brasil (1974-2014) - Té, Wilson Pedro [UNESP] (2015)
This dissertation covers relationships between Guinea-Bissau and Brazil, stated since 1974, when Guinea-Bissau conquered its independence from Portugal. Based on foreign policy, the political and diplomatic relationships will be analyzed technical cooperation: educational, cultural and military between Guinea-Bissau and Brazil. In the present study, we aim to demonstrate that relationships between the two countries had begun by wide expectations of either sides, but were frustrated in the first half of the 1990s. The debt crisis in Latin America, where Brazil is located, and the serious economic crisis that affected the feeble economy of Guinea-Bissau, have contributed to the downturn of the relationships between the two sides of the Atlantic. This research will be discussing how the technical cooperation has become one of the main pillars of these relationships, if not the most important. Lastly, the impacts of creation of the Community of Portuguese-Speaking Countries will be analyzed on the foreign policy of Guinea-Bissau in 1996, considered the bond in Guinea-Bissau's relationships with Brazil.